Failing Homeostasis of Quadriceps Muscle Energy- and pH Balance During Bicycling in a Young Patient With a Fontan Circulation - Haarman, Meindina G.; Vos, Johannes D. L.; Berger, Rolf M. F.; Willems, Tineke P.; Jeneson, Jeroen A. L. (Frontiers in Cardiovascular Medicine, 2019)
Aims: Patients with a congenital heart condition palliated with a Fontan circulation generally present with decreased exercise capacity due to impaired cardiopulmonary function. Recently, a study in patients with a Fontan circulation reported evidence for abnormal vascular endothelial function in leg muscle. We investigated if abnormal skeletal muscle hemodynamics during exercise play a role in the limited exercise tolerance of Fontan patients. If so, abnormalities in intramuscular energy metabolism would be expected both during exercise as well as during post-exercise metabolic recovery. Methods: In a young patient with a Fontan circulation and his healthy twin brother we studied the in vivo dynamics of energy- and pH-balance in quadriceps muscle during and after a maximal in-magnet bicycling exercise challenge using 31-phosphorus magnetic resonance spectroscopy. An unrelated age-matched boy was also included as independent control. Results: Quadriceps phosphocreatine (PCr) depletion during progressive exercise was more extensive in the Fontan patient than in both controls (95% versus 80%, respectively). Importantly, it failed to reach an intermittent plateau phase observed in both controls. Quadriceps pH during exercise in the Fontan patient fell 0.3 units at low to moderate workloads, dropping to pH 6.6 at exhaustion. In both controls quadriceps acidification during exercise was absent but for the maximal workload in the twin brother (pH 6.8). Post-exercise, the rate of metabolic recovery in the Fontan patient and both controls was identical (time constant of PCr recovery 32±4,31±2 and 28±4s, respectively). Conclusion: Homeostasis of quadriceps energy- and pH-balance during a maximal exercise test failed in the Fontan patient in comparison to his healthy twin brother and an age-matched independent control. Post-exercise metabolic recovery was normal which does not support the contribution of significant endothelial dysfunction affecting adequate delivery of oxidative substrates to the muscle to the lower exercise capacity in this particular Fontan patient. These results suggest that mitochondrial ATP synthetic capacity of the quadriceps muscle was intact but cardiac output to the leg muscles during exercise was insufficient to meet the muscular demand for oxygen. Therefore, improving cardiac output remains the main therapeutic target to improve exercise capacity in patients with a Fontan circulation.